2004
DOI: 10.1055/s-2004-832815
|View full text |Cite
|
Sign up to set email alerts
|

A Practical and User-Friendly Method for the Selenium-Free One-Step Preparation of 1,2-Diketones and their Monoxime Analogs

Abstract: P r e p a r a t i o n o f 1 , 2 -D i k e t o n e s a n d t h e i r M o n o x i m e A n a l o g s Abstract: Treatment of a-methylene ketones with excess sodium nitrite and aqueous HCl in THF at reduced temperatures provides an effective tool for the preparation of a variety of 1,2-diketones. The diastereoselective synthesis of the corresponding (Z)-1,2-dione monoximes could be accomplished under similar conditions, but by using only one equivalent of nitrosating reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
0
11
0
Order By: Relevance
“…The exposure of a well ground neat mixture of α-hydoxyimino ketone and o-phenylene diamine to microwave irradiation afforded the corresponding quinoxalines 20 as shown in Scheme 3a [43], while the plausible mechanism for the protonation of oxime group and intramolecular rearrangement was shown in Scheme 3b [43]. The α-hydoxyimino ketonic intermediate required for this study was acquired after slight modification of the earlier reported procedure by Rüedi and coworkers [44].…”
Section: <<<<>>>>mentioning
confidence: 99%
“…The exposure of a well ground neat mixture of α-hydoxyimino ketone and o-phenylene diamine to microwave irradiation afforded the corresponding quinoxalines 20 as shown in Scheme 3a [43], while the plausible mechanism for the protonation of oxime group and intramolecular rearrangement was shown in Scheme 3b [43]. The α-hydoxyimino ketonic intermediate required for this study was acquired after slight modification of the earlier reported procedure by Rüedi and coworkers [44].…”
Section: <<<<>>>>mentioning
confidence: 99%
“…The second series of diazoketones 2a-e was prepared using a modified approach, which involved nitrosation 21 of monoketones 6a-e followed by conversion of the resulting α-diketones 7a-e into tosylhydrazones 9a-e accompanied by the Bamford-Stevens reaction. 7,22 Nitrosation of ketones 6a-e was carried out with sodium nitrite in the presence of concentrated hydrochloric acid.…”
Section: Syn Thesismentioning
confidence: 99%
“…51 1,2-Cyclododecanedione 38 was achieved in a good yield, [52][53][54] by a variety of oxidation methodologies (Scheme 5): (a) by treatment of 1 with excess sodium nitrite and aq. HCl, 55 (b) through treatment of 2-hydroxycyclododecanone 35 with either DMSO/CF 3 COOH at -78 o C or Cu(OAc)/AcOH, (c) when 2-bromo-cyclododecanone 25 is oxidized using DMSO in presence of KI/K 2 CO 3 . Moreover, 38 was also obtained through chemical or photochemical oxidation of 2-(methylthio)cyclododecanone 36, 56 and 2-((dimethylamino)methylene)cyclododecanone 37, 57 respectively (Scheme 8).…”
Section: Ohmentioning
confidence: 99%